PEMBUATAN STIK PEPAYA UNTUK MENINGKATKAN PENDAPATAN KELUARGA DI DESA BULOTALANGI, KECAMATAN BULANGO TIMUR - Saman, Widya Rahmawaty; Isra, Muhammad; Ui, Nurwinda; Safriany, Dwy (Universitas Negeri Gorontalo, 2024)
Bulotalangi Village, located in Bulango Timur Subdistrict, Bone Bolango Regency, Gorontalo, is a horticultural production area, including papaya, with an average yield of 224 kg per year. Despite the abundant production, most of the harvest is sold fresh without further processing, resulting in low added value. To enhance community welfare, especially through food diversification, a community empowerment program was implemented in the form of training to produce papaya sticks. This program was designed to equip the community, particularly housewives, with technical skills in papaya processing, business management, and marketing strategies. The training included selecting high-quality raw materials, hygienic production processes, and packaging techniques that meet market standards. Survey results showed that the majority of participants (90%) were women, with a dominant age range of 41–50 years (70%), high school education (60%), and working as entrepreneurs (90%). About 80% of participants preferred the spicy flavor variant of papaya sticks, and 100% stated that the product appearance was attractive. Additionally, the training successfully improved participants' understanding of business opportunities based on papaya processing. Post-training surveys noted that 90% of participants felt optimistic about the market potential of this product. Through this processing innovation, papaya sticks are expected to become a sustainable new source of income, support food security, and improve the welfare of the Bulotalangi Village community. The sustainability of this program requires support in the form of access to capital and broader marketing strategies.